Food Inflation in Brazil in the Last Decade – Comparing Evolution Trends Before and During the COVID-19 Pandemic - de Oliveira, Jonatan Alexandre [UNESP]; Baccarin, José Giacomo [UNESP]; Da Silva Costa, Eduarda Pires Valente (My University, 2024)
The objective is to characterize food inflation in general and, particularly, the food items and agrifood chains, according to the level of exposure to foreign trade, degree of processing, and inflation indicators in nine metropolitan areas of Brazil between 2007 and 2022. Basically, the data used were surveyed by the Brazilian Institute of Geography and Statistics for the Broad Consumer Price Index (Índice de Preços ao Consumidor Amplo, IPCA). The study fully characterized the food inflation in Brazil between 2007 and 2022, which was aggravated during the Covid-19 pandemic. Food-at-home inflation was generalized among its household components. Items associated with animal protein tended to put the most pressure on food-at-home prices. Among the agrifood chains, the lowest price variations were observed in products with greater exposure to foreign trade. A greater price variation was observed for fresh or minimally processed food products compared to more processed food products. Among the nine cities studied, from all regions of Brazil, no major differences were found in the variations of food prices of all groups considered.
Keywords: agricultural internationalization; consumer inflation; food prices